Strength and fatigue analysis of periodic perforated materials using the computational homogenization and ES-FEM approaches - Nguyen, Phuong H.; Le, Canh V.; Ho, Phuc L.H. (Vietnam Journal of Mechanics, 2022)
This paper presents a computational homogenization shakedown analysis of periodic perforated materials with von Mises matrices. The plastic behaviors of the perforated materials under cyclic macroscopic loads are studied by means of kinematic shakedown theorem and computational homogenization method. The kinematic micro-fields are approximated by the edge-based smoothed finite element method. The resulting large-scale optimization problem is efficiently solved by using conic solver, enabling a large number of points on the macroscopic strength and fatigue surface to be calculated rapidly. The effects of the hole's shape and size on the overall strength and fatigue domains are also investigated.